Super Stability of Ag Nanoparticle in Crystalline Lamellar (Lc) Liquid Crystal Matrix at Different pH Environment - Mohd Yasin, Siti Mariah; Badruddin, Irfan Anjum; Johan, Mohd Rafie (MDPI, 2019)
The symmetry concept in this paper is related to the natural self-assembly of noble metal nanoparticles in the long range periodic structure of liquid crystal (LC). The current study deliberates the effect of pH on the stability of nanoparticles (NPs) in the lamellar phase of a lyotropic LC environment. The LC was prepared by the mass ratio 0.33:0.22:0.45 for (HDTABr):1-pentanol:water. The LC containing silver nanoparticles (AgNPs) was prepared by replacing the water with Ag solution. The AgNPs were produced by the in situ preparation method in LC. The solution of AgNPs-LC was varied at different pH. The absorption intensities were determined by using ultra-violet spectroscopy (UV-vis). The surface potential and hydrodynamic particle size were determined by using Zeta-potential (measurements). The surface enhanced Raman spectroscopy (SERS) was carried out to enhance the Raman signals of 4-aminobenzenethiol (4-ABT) deposited onto AgNPs as substrate. It is found that all characterizations exhibited super stability for AgNPs dispersed in LC at pH = 3 to 12 with the optimum stability at pH = 5-6. The remarkable stability of NPs is an important indicator of the various applications in nanotechnology and nanoscience fields. © 2019 by the authors.